Introduction of Automatic Wooden Bridge Load Testing Detector For Pedestrians Using Load Cell Sensor - Kurnia Paranita Kartika Riyanti; Nurjanah; Hazairin Nikmatul Lukma (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this long-term research is to study further about the application of automatic detectors for testing the bridge strength load using a load cell sensor. Therefore, it is necessary to test the use of small-scale on miniature bridges with various materials. Next is the scaling on the actual bridge. The research method used is Research and Development (RnD), starting from data collection with observations and interviews, system design, assembly and trial use and scaling calculations so that they can be implemented on the actual bridge. The object of research is various miniature bridges in the Civil Engineering laboratory of the Islamic University of Balitar. While its implementation was then carried out at the Blitar Settlement and City Planning Service. Data analysis was carried out using qualitative methods, by reducing data, presenting data and drawing conclusions on an ongoing basis. Testing the detector is carried out with two types of loads, namely static and dynamic, in testing the detector with a static load, the detector can read the load with a suitability close to 100%. In testing the detector with a running load, the reading results are divided into several loadcells that are passed by the load, with the largest load reading on the loadcell that is the load (point load). The result of the error percentage on the average running load is 4.67%. The read load on the bridge is smaller than the actual weight because some of the load is accepted by the bridge supports and bridge boards.